(untitled) (Homoeopathy for All, 2024)
Agro-homoeopathy is a newly developing science with many benefits. Homoeopathic medicines act as powerhouse of energy, transferring the essence of medicines into the parts that come in their contact. An extensive research and study required in the field of agro-homoeopathy to elicit the effectiveness of various homoeopathic medicines. The medicines are used in potentized form, mixed with water in various methods. Homoeopathic medicines thus revamp and preserve the soil strength, rectify the pathological changes in plants and take the edge off the fertilizers or pesticides.